PERSEPSI MASYARAKAT DAN KAJIAN STRATEGI PENGEMBANGAN BIOGAS TERHADAP TEKNOLOGI BIOGAS DARI KOTORAN TERNAK SAPI DI KABUPATEN BANJAR - Vardi, Lulu Vila; Biyatmoko, Danang; Sulaiman, Abrani; Yusriadi, Yusriadi (EnviroScienteae, 2024)
The Banjar district government has provided assistance to livestock communities and slaughterhouses to develop this biogas in order to reduce the impact of environmental pollution. The success of this development may depend on the perception of the farming community. Based on this, the aim of this research is to analyze and formulate a biogas development strategy and analyze public perceptions regarding the development of biogas technology from cow manure in Banjar Regency. This research was carried out in Banjar Regency with 4 (four) observation locations, namely Martapura Kota, Pengaron, Sungai Pinang and Mataraman Districts. This research was carried out with a SWOT analysis to find a suitable development strategy for biogas development in Banjar Regency and used descriptive analysis to explain the perceptions of the livestock farming community and non-breeding community towards the technology. biogas in Banjar Regency. Results show that 69.5% of both livestock and non-livestock communities strongly agree that untreated cow dung causes environmental pollution and disease. Additionally, 54.5% support converting manure into biogas, and 65% acknowledge the limited processing of biogas. The SWOT analysis places biogas development in quadrant I, indicating that the strategy should leverage Strengths to capitalize on opportunities (S-O). The recommended approach involves using the ample cattle population to reduce pollution and leveraging government support to enhance biogas facilities and infrastructure.